2016
DOI: 10.1590/1678-775720160099
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of dental pulp stem cells with Biodentine and MTA after exposure to different environments

Abstract: Objective:The aim of the present study was to evaluate and compare the cytotoxic effects of Biodentine and MTA on dental pulp stem cells (DPSCs) and to assess cell viability and adherence after material exposure to an acidic environment.Material and Methods:DPSCs were cultured either alone or in contact with either: Biodentine; MTA set for 1 hour; or MTA set for 24 hours. After 4 and 7 days, cell viability was measured using the MTT assay. Biodentine and MTA were also prepared and packed into standardized bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 31 publications
(45 reference statements)
1
27
0
4
Order By: Relevance
“…MTA can form a hard tissue barrier at the exposed site of pulp, and effectively prevent bacterial leakage [17]. Despite its safety and efficacy, MTA has certain drawbacks, such as poor operability, tooth staining, long setting time, and high cost [39], possibly leading to pulp diffuse calcific deposition and finally resulting in pulp chamber and canal obliteration [1]. In this study, CGF provided evidences that the application of CGF for pulp capping is more similar to the physiological state than are Ca(OH) 2 and MTA.…”
Section: Discussionmentioning
confidence: 99%
“…MTA can form a hard tissue barrier at the exposed site of pulp, and effectively prevent bacterial leakage [17]. Despite its safety and efficacy, MTA has certain drawbacks, such as poor operability, tooth staining, long setting time, and high cost [39], possibly leading to pulp diffuse calcific deposition and finally resulting in pulp chamber and canal obliteration [1]. In this study, CGF provided evidences that the application of CGF for pulp capping is more similar to the physiological state than are Ca(OH) 2 and MTA.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro DPC model, BD showed the potential to preserve hDPSC proliferation, migration, and adhesion [17]. Moreover, previous studies comparing the effects of MTA and BD reported that BD accelerated hDPSC proliferation in comparison to MTA [18,19]. TC has been shown to result in superior cell viability of hDPSCs compared to calcium hydroxide [20].…”
Section: Introductionmentioning
confidence: 98%
“…13,14 MTA Fillapex is a new calcium carbonate-based sealer with an excellent affinity for MTA-based materials due to MTA's superb biocompatibility, bioactivity, and osteoconductivity. 15 In 2001, MTA Angelus was introduced as a modified form of ProRoot MTA and was used in specific areas. One of the significant differences between ProRoot MTA and MTA Angelus is the absence of dehydrated calcium sulfate, one of its most important ingredients, so that MTA Angelus has a shorter setting time compared to ProRoot MTA.…”
Section: Introductionmentioning
confidence: 99%